Prescriptive and descriptive norms in second person singular forms of address in Argentinean Spanish: Vos, usted, tú - Garcia Negroni, Maria Marta (2020)
In this chapter, we analyze and compare the use of second person singular terms of address (vos/usted/tú) in Argentinean mass-consumption audiovisual and printed texts from two different periods (1960 and 2015). Using the distinction between prescriptive and descriptive norms (axiological and objective in Blanco 2000), we show that the paradigm of the former has changed over the last fifty years and now overlaps with the latter. However, there is still a gap between both norms: the use of tú/contigo and the voseo reforzado (“double” voseo) in present subjunctive. We propose an explanation for both phenomena in terms of social proximity and symbolic identity.